Geopolitics and the Oil Price - Noguera-Santaella, J (Elsevier, 2016)
This paper digs into the relationship between armed and civil conflicts and oil prices. If conflicts threaten oil supply reliability, even if disruption does not actually occur, this should be reflected in prices, if expectations react accordingly. For this purpose, using monthly data since 1859, we conduct an intervention time series analysis to study the effect of 32 different geopolitical events on real oil prices. The geopolitical events considered go from the American Civil War to the recent Arab Spring episodes. We find that geopolitical events positively affected oil prices before the year 2000, but have had little impact, if any at all, afterwards. © 2015 Elsevier B.V.